The impact of foreign direct investment inflows on unemployment and economic growth in West Africa - Ikani, Kingsley Success (Nurture, 2024)
Purpose: This study explores the short- and long-run effects of foreign direct investment inflows (FDI) on both the unemployment rate and economic growth in West Africa utilizing a panel dataset spanning from 1991 to 2022. The precise impact of FDI on these variables and the underlying factors shaping this relationship in West Africa has not been definitively delineated. Previous literature has not exclusively delved into the impact of FDI on the unemployment rate in this region. Consequently, our paper endeavors to address this particular gap in knowledge concentrating on the individual countries within West Africa. Design/Methodology/Approach: We employ Pooled Mean Group (PMG) estimators and fixed effects models for our analyses. Findings: Our findings based on the PMG models unveil that FDI exhibits an insignificant positive long-term effect and a highly significant negative short-term impact on economic growth in West Africa. Similarly, we observe that the impact of FDI on the unemployment rate is negative both in the long- and short-term. Conclusion: Our findings demonstrate that various factors contribute to how FDI influences the unemployment rate and economic growth rate in West Africa. Research Limitation: The results of these models analyses are subject to the considered economic variables. Other economic variables could give different results. Practical Implication: The research findings imply that FDI cannot be relied upon as a comprehensive strategy to either stimulate economic growth or alleviate unemployment in the Western Africa region.